Baseline parameters for rotational thromboelastometry (ROTEM®) in healthy women undergoing elective caesarean delivery: a prospective observational study in Australia. (May 2019) - Lee, J.; Eley, V.A.; Wyssusek, K.H.; Coonan, E.; Way, M.; Cohen, J.; Rowell, J.; van Zundert, A.A.
Highlights: Rotational thromboelastometry reference ranges were established in term pregnancies. Measures of clot firmness were higher than non-obstetric reference ranges. Times to clotting onset were shorter than non-obstetric reference ranges. ROTEM® reference ranges in pregnant women were different to non-obstetric values. Abstract: Background: Formal reference ranges for rotational thromboelastometry (ROTEM®) in pregnancy have not been obtained in the recommended minimum sample size of 120. This prospective observational study aimed to establish baseline parameters in an Australian population of women undergoing elective caesarean delivery. The secondary aim was to compare these reference ranges with those from prior studies and the manufacturer. Methods: Women undergoing elective caesarean delivery at term were included if they were at term, of normal body mass index and had no conditions affecting coagulation. ROTEM® reference ranges were derived by calculating the 2.5 and 97.5 percentiles for INTEM/EXTEM/FIBTEM amplitude at 5 minutes (A5), amplitude at 15 minutes (A15), coagulation time (CT), maximum clot firmness (MCF), and clot formation time (CFT). Results: Of 202 women screened, 132 met the inclusion criteria, having a mean age of 32.7 ± 5.0 years and median body mass index of 23.8 kg/m 2 (interquartile range 21.5–26.4). The reference ranges for selected ROTEM® parameters were as follows: FIBTEM A5 (13–28 mm), FIBTEM CT (40–74 s), FIBTEM MCF (16–34 mm), EXTEM A5 (39–66 mm), EXTEM CT (43–69 s), INTEM A5 (38–63 mm). Conclusions: ROTEM® reference ranges for women with uncomplicated term pregnancies were reported as per the International Federation of Clinical Chemistry. The FIBTEM MCF and FIBTEM/EXTEM/INTEM amplitudes were higher in comparison to the manufacturer's reference ranges for the non-obstetric population. The EXTEM CT was shorter than the non-obstetric reference ranges. These ranges show an increase in coagulability during normal pregnancy compared to the non-pregnant reference ranges.